Marketing Overload: The Impact of Information Overload on Brand Recall (A Case Study of Students of the University of Swat) (Journal of Social Sciences Review, 2023)
Marketers promote their products using a different medium to circulate their advertising message to customers in order to inform and persuade customers to buy their products. The emergence of new technology and social media platforms has made it much easier for marketers to reach more audiences than ever before. This excessive advertisement has emerged as a new phenomenon known as infobesity, advertising overload, or marketing overload. The purpose of this study is to find out the effect of Information overload on brand recall, for which a quantitative method was used with a sample size of 148 students and SPSS 21 for analysis of the data. The survey was conducted, and questionnaires were distributed among the students of the University of Swat. The study reveals that a negative and significant relationship exists between information overload and brand recall. This study also reveals that excessive bombardment in advertisements results in a decline in the effectiveness of the advertising message and goes against brand awareness and brand recall. The correlation analysis (r= -0.353, P
Keywords: Information Overload; Brand Recall; Marketing Overload; Advertising Clutter